Accuracy of the corner coordinates of a building surveyed with nine points in RTK GNSS method - Pırtı, Atınç; Eren, Mehmet; Hoşbaş, Ramazan Gürsel (Geodesy and Cartography, 2025)
In this study, measurements were made to compute the coordinates of a building’s corner with only one steel tape measure and two GNSS receivers in the field. First, three circle arcs were drawn in the field using a steel tape measure at a distance of 1 meter, 3 meters and 5 meters from the corner of the building, and three points were marked spontaneously on each of these three arcs. A total of nine points were obtained and the coordinates of these nine points were determined by using RTK GNSS technique. The coordinates of the corner of the building (K1) were computed by using the coordinates of nine points on 1 meter, 3 meter and 5 meter circle arcs. In this calculation process, the coordinates of the building corner are obtained by taking the average of the values by using nine points on the three circle arcs. When the building corner coordinates obtained with the total station and the coordinates obtained by marking nine points on the arcs were compared, the maximum and minimum differences were found in the range of 5–6 centimetre. Considering that it is advantageous in terms of time, this new method takes completely about 85 minutes for all of the points.